Blood Pressure Management for Ischemic Stroke in the First 24 Hours. Issue 4 (16th March 2022) - Bath, Philip M.; Song, Lili; Silva, Gisele S.; Mistry, Eva; Petersen, Nils; Tsivgoulis, Georgios; Mazighi, Mikael; Bang, Oh Young; Sandset, Else Charlotte
Abstract : High blood pressure (BP) is common after ischemic stroke and associated with a poor functional outcome and increased mortality. The conundrum then arises on whether to lower BP to improve outcome or whether this will worsen cerebral perfusion due to aberrant cerebral autoregulation. A number of large trials of BP lowering have failed to change outcome whether treatment was started prehospital in the community or hospital. Hence, nuances on how to manage high BP are likely, including whether different interventions are needed for different causes, the type and timing of the drug, how quickly BP is lowered, and the collateral effects of the drug, including on cerebral perfusion and platelets. Specific scenarios are also important, including when to lower BP before, during, and after intravenous thrombolysis and endovascular therapy/thrombectomy, when it may be necessary to raise BP, and when antihypertensive drugs taken before stroke should be restarted. This narrative review addresses these and other questions. Although further large trials are ongoing, it is increasingly likely that there is no simple answer. Different subgroups of patients may need to have their BP lowered (eg, before or after thrombolysis), left alone, or elevated.